The role of word formation manners in the creation of adjectives in the Albanian language - Duraj, Petrit (Technium Social Sciences Journal, 2022)
This part of the speech has been enriched and is constantly being enriched with new words, both from other parts of the speech and from the adjective class itself. The most productive ways of adjective word formation are origin (affixation, articulation, articulation and affixation at the same time), composition and structure.Initial adjectives are those adjectives, which today are unanalyzable in their constituent parts, neither a word-forming theme nor a word-forming formant can be investigated. Besides type adjective: alive, evil, good, first, young, here also enter all the adjectives of foreign origin, which within Albanian are unresolvable in their constituent elements, eg: absolute, banal, decadent, elegant, naive, real etc.Derivative adjectives are those adjectives, when in present Albanian the source can be investigated, derivation from another word with the participation of different word-forming morphemes. Thus, these adjectives are resolvable, analyzable in their constituent elements. Here are distinguished derivative adjectives with: a) prefixation, b) suffixation, c) articulation and suffixation simultaneously, and d) articulation, prefixation and suffixation simultaneously.Our paper aims to give an insight into the types of adjectives according to the mode of word-formation, as well as their use in different grammatical circumstances.Keywords: typology, part of speech, adjective, word-formation.